1992
DOI: 10.1063/1.463157
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of AlAr and AlKr from 31 000 cm−1 to the ionization limit

Abstract: New singlet Rydberg states of the NH(ND) radical in the energy range 92000-100000 cm−1 characterized by resonance enhanced multiphoton ionizationphotoelectron spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…24,25 In these complexes, as well as AlRg (Rg ) rare gas) complexes, excitation of the atom causes a large change in the binding energy and Al-M equilibrium atom-molecule separation and hence results in considerable Franck-Condon activity in the van der Waals stretch mode. [24][25][26] The series of bands of Al-CH 4 displayed in Figure 1a,b is similarly assigned to the Al-CH 4 stretch progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In these complexes, as well as AlRg (Rg ) rare gas) complexes, excitation of the atom causes a large change in the binding energy and Al-M equilibrium atom-molecule separation and hence results in considerable Franck-Condon activity in the van der Waals stretch mode. [24][25][26] The series of bands of Al-CH 4 displayed in Figure 1a,b is similarly assigned to the Al-CH 4 stretch progression.…”
Section: Resultsmentioning
confidence: 99%
“…Several electronic states of the complex can emanate from the degenerate atomic asymptote Al(4d) + CH 4 /CD 4 , as has been observed for AlRg complexes. 26 In these diatomic complexes, the binding energies have the ordering 2 ∆ > 2 Π > 2 Σ + , as expected from simple arguments concerning the minimization of nonbonding electron repulsion. One possibility is that the bands of Al-CH 4 /CD 4 near 38 600 cm -1 involve excitation of a less strongly bound electronic state of the complex correlating to the Al(4d) + CH 4 /CD 4 asymptote than does the state associated with the van der Waals stretch progression.…”
Section: The 4d R 3p Transitionmentioning
confidence: 91%
“…This same logic has also been applied to van der Waals complexes of the group IIIA metals ͑e.g., Al,In͒, except that the ground/excited state pattern seen for the alkalis is inverted in the 2 ⌺← 2 ⌸ band systems studied for the group IIIA complexes. [13][14][15][16][17][18][19][20][21][22] The noble metals are expected to be more polarizable than the lighter metals studied to date, enhancing the van der Waals interactions. The spin-orbit interactions are also expected to be more pronounced in the noble metals than they are in the alkalis or lighter group IIA systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] While complexes of the heavier atoms in this group ͑Ga, 11 In, 12,13 Tl 14,15 ͒ have also been investigated, those involving aluminum have received the most attention. [16][17][18][19][20][21][22] Gardiner and Lester 16 reported the first observation of the AlAr complex using resonance enhanced multiphoton ionization ͑REMPI͒ through the B 2 ⌺ ϩ -X 2 ⌸ 1/2 electronic transition, which correlates with the Al atomic 4s←3p transition. Callender et al 17 reported laser fluorescence excitation spectra of the complexes of Al with the heavier noble gases, and employed resolved emission spectra to characterize the vibrational spacings in the ground electronic states of AlAr, AlKr, and AlXe.…”
Section: Introductionmentioning
confidence: 99%